Effectiveness and cost-effectiveness of school-based dissemination strategies of an internet-based program for the prevention and early intervention in eating disorders: a randomized trial - Moessner, Markus; Minarik, Carla; Özer, Fikret; Bauer, Stephanie (Prevention science, 2016)
Only little is known about costs and effects (i.e., success) of dissemination strategies, although cost-effective dissemination strategies are crucial for the transfer of interventions into routine care. This study investigates the effects and cost-effectiveness of five school-based dissemination strategies for an Internet-based intervention for the prevention and early intervention of eating disorders. Three-hundred ninety-five schools were randomly assigned to one of five dissemination strategies. Strategies varied with respect to intensity from only sending advertisement materials and asking the school to distribute them among students to organizing presentations and workshops at schools. Effects were defined as the number of page visits, the number of screenings conducted, and the number of registrations to the Internet-based intervention. More expensive strategies proved to be more cost-effective. Cost per page visit ranged from 2.83€ (introductory presentation plus workshop) to 20.37€ (dissemination by student representatives/peers). Costs per screening ranged from 3.30€ (introductory presentation plus workshop) to 75.66€ (dissemination by student representatives/peers), and costs per registration ranged from 6.86€ (introductory presentation plus workshop) to 431.10€ (advertisement materials only). Dissemination of an Internet-based intervention for prevention and early intervention is challenging and expensive. More intense, expensive strategies with personal contact proved to be more cost-effective. The combination of an introductory presentation on eating disorders and a workshop in the high school was most effective and had the best cost-effectiveness ratio. The sole distribution of advertisement materials attracted hardly any participants to the Internet-based program.
Published online: 19 November 2015
Gesehen am 11.02.2020